Implementasi Logika Fuzzy pada Alat Cuci Tangan Otomatis Portabel dengan Sistem Monitoring Berbasis Android - Hari Setyo Permadi; Mohammad Ridwan; Febri Rismaningsih (Jurnal Buana Informatika, 2021)
Abstract. Fuzzy Logic Implementation on A Portable Automatic Handwashing Station with An Android-Based Monitoring System. When the COVID-19 pandemic hit the world and Indonesia, washing hands with soap was the first step to prevent the virus from entering the body. The hand washing facilities used by the community are still operated by hand. This creates an opportunity for the virus to spread. This study aims to create a hand washing facility using ultrasonic and Arduino sensors to avoid touching method in its operation, and a monitoring system with Android to monitor waste, water and soap which is equipped with features facilitating the maintenance system. This study implemented fuzzy logic in determining the engine ignition reaction with the hand distance indicator to the sensor. The result of testing the accuracy of the ultrasonic sensor to read hand distance is 92.65%.Keywords: Fuzzy Logic, Android, Handwashing Station Abstrak. Saat pandemi COVID-19 melanda dunia dan Indonesia, mencuci tangan dengan sabun merupakan langkah awal pencegahan virus masuk ke dalam tubuh. Sarana cuci tangan yang digunakan oleh masyarakat masih dioperasikan dengan tangan. Hal tersebut menyebabkan peluang penyebaran virus. Penelitian ini bertujuan membuat alat cuci tangan menggunakan sensor ultrasonik dan Arduino untuk menghidari metode sentuh pada pengoprasiannya, dan sistem monitoring dengan Android untuk memantau limbah, air dan sabun yang dilengkapi dengan fitur yang memudahkan sistem perawatan. Penelitian ini menggunakan logika Fuzzy dalam menentukan reaksi penyalaan mesin dengan indikator jarak tangan ke sensor. Hasil pengujian keakuratan sensor ultrasonik untuk membaca jarak tangan ialah 92.65%. Kata Kunci: Logika Fuzzy, Android, Alat Cuci Tangan